The The Fiction System in the Mexican Press in the Early Twentieth Century: Reading and Materiality (Anclajes, 2022)
The phenomenon of the fictionalization of journalistic writing will be explored, by following Marie-Ève Thérenty and Sarah Mombert, who analyze this discursive process in which the reality, the facts themselves, are treated as fiction in journalistic genres such as the chronicle, the fait-divers, the travel story, the reportage and, even, the interview. These textual exchanges, which will problematize the relationship between journalistic writing, fiction and reality, are the issues that will be examined in some Mexican newspapers of the early Twentieth Century. To this analysis it will be added the consideration of material conditions and reading practices as possible indicial elements of the phenomenon.
Keywords: Newspaper press; fiction; writing; Newpaper readership; Mexico